Key mechanistic features of swelling and blistering of helium-ion-irradiated tungsten. (15th March 2020) - Allen, Frances I.; Hosemann, Peter; Balooch, Mehdi
Graphical abstract: Abstract: Helium-ion-induced swelling and blistering of single-crystal tungsten is investigated using a Helium Ion Microscope for site-specific dose-controlled irradiation (at 25 keV) with analysis by Helium Ion Microscopy, Atomic Force Microscopy and Transmission Electron Microscopy (cross-sectioning by Focused Ion Beam milling). We show that the blister cavity forms at a depth close to the simulated helium peak and that nanobubbles coalesce to form nanocracks within the envelope of the ion stopping range, swelling the blister shell. These results provide the first direct experimental evidence for the interbubble fracture mechanism proposed in the framework of the gas pressure model for blister formation.